Alternative of Soil and Water Conservation Techniques in Cilemer Watershed, Banten: Alternatif Teknik Konservasi Tanah dan Air untuk DAS Cilemer, Banten - Nursari, Evi; Rachman, Latief Mahir; Baskoro, Dwi Putro Tejo (Jurnal Ilmu Tanah dan Lingkungan, 2018)
Floods and droughts are routine problems that occur in Cilemer Watershed due to their decrease in quality. Application of Soil and Water Conservation (SWC) is one solution to improve the quality of Cilemer Watershed. A study aimed to simulate several SWC, obtain alternative of SWC and provides the best watershed management directions was carried out Cilemer Watershed. The research was carried out in several stages: (i) secondary data collection, (ii) field survey (primary data collection), (iii) data analysis, (iv) running SWAT model, (v) SWC simulation with SWAT model, (vi) watershed management scenarios, and (vii) arrangement of watershed management directives. The result shows that the application of SWC can improve watershed quality which is characterized by decreases Qmax/Qmin ratio and direct runoff but increases base flow and water yield. Application of mini traditional reservoir is the best watershed management scenario. This scenario is able to decrease the direct runoff, but increase base flow and water yield much greater than other scenarios. Application of mini traditional reservoir decreses direct runoff by 29.24%, where the coefficient of runoff decreases from 0.25 (existing condition) to 0.17. In addition, the scenario can also increase base flow by 46.00% (from 357.5 mm to 522.0 mm) and water yield by 3.99%. Water yield increase from 904.5 mm (existing condition) to 941.0 mm.